Animated Video Learning Improves Elementary Students Electrical Circuit Understanding: Pembelajaran Video Animasi Meningkatkan Pemahaman Rangkaian Listrik Siswa SD - Ryanda, Ergi; Khoiri, Ahmad (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Elementary education requires appropriate instructional media to support student understanding and engagement, particularly within integrated science learning (IPAS). Specific Background: Learning about simple electrical circuits is often challenging for elementary students due to its abstract and dynamic nature, while classroom practices remain dominated by limited and less interactive media. Knowledge Gap: Although animated video has been widely recognized in science education, there is limited empirical evidence focusing on its application in IPAS learning on simple electrical circuits for fifth-grade students and its role in addressing conceptual understanding and classroom engagement. Aims: This study aims to examine the use of animated video in improving student learning outcomes on simple electrical circuit concepts among fifth-grade students at SDN 1 Pinoh Utara. Results: Using a one-group pretest-posttest design with 20 students, the findings reveal a statistically significant increase in learning outcomes after the intervention (t_count = 30.241 > t_table = 1.734; p < 0.05), indicating measurable improvement in students’ cognitive achievement. Novelty: The study applies Cognitive Theory of Multimedia Learning principles within IPAS context to directly measure learning outcomes and conceptual understanding of abstract scientific processes in elementary education. Implications: Animated video learning provides a practical instructional approach that supports active participation, accommodates diverse learning styles, and facilitates clearer understanding of abstract concepts, offering valuable guidance for improving science teaching strategies in primary schools. Highlights• Significant gain in posttest scores demonstrates measurable learning progress• Multimedia-based instruction supports active classroom participation• Visual representation clarifies abstract scientific processes for young learners KeywordsAnimated Video; Learning Outcomes; Electrical Circuits; Elementary Education; Multimedia Learning